A Different Perspective on ›Made in America‹ (KULT_online, 2010)
Whereas Werner Sollors' and Greil Marcus' New Literary History of America tries explicitly not to offer any redefinitions of what does and does not constitute a canon of American literature, it nevertheless offers its readers a fresh kaleidoscopic look on US-American culture from its beginnings in the 15th century up to the election of President Obama in 2008. In doing so, it investigates canonized authors, texts and historical moments, but also casts a look at the margins of US-American literary and cultural history. The compendium's main strength however is the high quality of its more than two hundred original essays written by renowned experts in respective fields.